Systems everywhere?. (23rd April 2019) - Vanderstraeten, Raf
Abstract: Ludwig von Bertalanffy built his hopes for system theory on the growing visibility of systems in the world. The first introductory section of the 1968 edition of General System Theory is titled "Systems Everywhere." Half a century later, system theory has fallen into disrepute in several fields of study. It is targeted for its technocratic and governmental ambitions; it is depicted as an attempt to understand and reshape the world according to the system image of the world. This paper sketches how the social world has been analysed as a system—with a focus on hierarchy, predictability, and control. It proceeds to show how Von Bertalanffy's emphasis on the distinction between system and environment allows for the analysis of heterogeneity, indeterminacy, and uncontrollability. This paper thus makes a plea for a reflexive theory that focuses on problems that emerge despite the fact that our society imagines itself as a system.